THE EFFECT OF LABORATORY FACILITIES AND TEACHER COMPETENCE ON STUDENT LEARNING OUTCOMES IN VOCATIONAL HIGH SCHOOL (VHS) - Elmunsyah, Hakkun; Rizza, Muhammad (Universitas Negeri Malang, 2018)
Learning in VHS cannot be separated from teacher?s role as an educator. Besides that, the laboratory is necessary to support the life skill, critical and creative thinking, collaborating, communicating, and literacy. It can be concluded that there is a strong relationship between laboratory infrastructure (X1) and teacher competence (X2) on student learning outcomes (Y). The case study in this research known results as follows: (1) there are significantly impact between variable X1 and Y, (2) there are significantly impact between variable X2 and Y, (3) there are there are significantly impact between laboratory facilities and teacher competence with student?s learning outcomes.